Treatment and Valorisation of Pomace Olive Oil Wastewater - Martins, Ramiro (2023)
Wastewater generated during the production of pomace olive oil is complex and highly variable due to different cultivation and processing characteristics. It has a high toxic organic load, low pH, and high chemical and biological demands. To reduce the concentration of chemical oxygen demand (COD) and total phenolic compounds (TPh) in pomace olive oil wastewater, several treatment processes have been studied. These include: (i) coagulation/flocculation, (ii) electrocoagulation, (iii) peroxy-electrocoagulation, (iv) electrochemical peroxidation, (v) Fenton, (vi) electro-Fenton, (vii) photo-Fenton, and (viii) adsorption. Coagulation/flocculation and electrocoagulation resulted in a maximum COD removal of 16%, while techniques involving the addition of hydrogen peroxide (iii-vii) had an average of 78% TPh removal but only 20% COD removal. Adsorption resulted in a maximum of 29% COD and 75% TPh removal. None of the tested techniques were able to remove more than 50% of COD, indicating the difficulty of removing organic matter in this effluent. However, advanced oxidation techniques were effective in degrading phenolic compounds, although they required relatively high dosages of oxidant.